Paradoxical Formation of Legislation as a Manifestation of Law from the Perspective of Power and Justice - Rido Pradana (Law Development Journal, 2026)
The formation of legislation is a manifestation of a state of law where the highest power lies in the law, not power as regulated in Article 1 paragraph (3) of the 1945 Constitution of the Republic of Indonesia. In the formation of legislation, the state of law is based on democracy which means the people hold a key role and a central position in determining the direction of policy, but in reality there are laws and regulations that are the result of the product of state power in the field of legislation that are not in accordance with the voice of the people. This research will discuss how the formation of legislation as a manifestation of law and the formation of legislation from the perspective of power and justice. By using a normative juridical research method, the author uses a statutory approach which is carried out by examining all laws and regulations that are interconnected with the legal issues discussed based on primary, secondary, and tertiary legal materials. The results of this study indicate a paradox in the formation of legislation as a manifestation of applicable law, from the perspective of power the formation of legislation is not carried out on the basis of the principles of the formation of good and correct legislation in order to create legal objectives and from the perspective of justice the legislation is not able to fulfill the aspirations of the community to become a real program that has a good impact on society. To avoid the paradox of the formation of legislation as a manifestation of law made by the state from the perspective of power and justice, it is necessary to apply the doctrine of meaningful participation optimally in the system of formation of legislation as a form of fulfillment of the principle of people's sovereignty.